Uwagi na temat pojęcia "użyteczność publiczna" - Wojciechowski, Eugeniusz (The Concept of Public Utility : Some Remarks, 2005)
The article concerns the role of public utility in the economic activity. The considerations present broad outlines of the topic and only indicate this problem. Public utility preserves autonomy closely connected with the realization of basic public functions. As the whole the article points to some problems and provokes into discussion on this topic. The content of the paper are the comments and remarks related to chosen elements of public utility as an economic category.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 276-282